2016
DOI: 10.1159/000447632
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase 14 Promotes Cell Proliferation, Migration and Invasion in Ovarian Cancer by Inhibiting Wnt Signaling Pathway

Abstract: Objective: The study aimed to investigate cyclin-dependent kinase 14 (CDK14) and its co-function with Wnt signaling pathway on cell proliferation, migration and invasion in ovarian cancer. Methods: CDK14 expressions were detected by quantitative real-time polymerase chain reaction. The expressions c-Myc, cyclinD1, PFTK1, ki67 and OGT were examined by Western blot. MTT assay was applied to observe cell proliferation after transfection of pEGFP-N1/CDK14-siRNA and pEGFP-N1 into SKOV3 cells, and scratch test and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…Even though sufficient sensitivity and specificity cannot be obtained solely by immunohistochemical examination, in a clinical setting, such examination using formalin-fixed paraffin-embedded tissue specimens of surgically resected material would be an auxiliary procedure for ER risk diagnosis based on quantification of DNA methylation. CDK14 reportedly participates in the proliferation and invasion of many tumor cells, including those of breast cancer (Imawari et al 2018), glioma (Fan et al 2015), hepatocellular carcinoma (Tu et al 2019), and ovarian cancer (Ou-Yang et al 2017). In pancreatic cancers, CDK14 has been revealed as a hub gene in the interaction network including the Wnt/β-catenin pathway and phosphoinositide 3-kinase/Akt signaling pathway, and its increased expression is associated with poorer overall patient survival (Yuan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even though sufficient sensitivity and specificity cannot be obtained solely by immunohistochemical examination, in a clinical setting, such examination using formalin-fixed paraffin-embedded tissue specimens of surgically resected material would be an auxiliary procedure for ER risk diagnosis based on quantification of DNA methylation. CDK14 reportedly participates in the proliferation and invasion of many tumor cells, including those of breast cancer (Imawari et al 2018), glioma (Fan et al 2015), hepatocellular carcinoma (Tu et al 2019), and ovarian cancer (Ou-Yang et al 2017). In pancreatic cancers, CDK14 has been revealed as a hub gene in the interaction network including the Wnt/β-catenin pathway and phosphoinositide 3-kinase/Akt signaling pathway, and its increased expression is associated with poorer overall patient survival (Yuan et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that cyclin Y and CDK14 could interact at the membrane to modulate LRP6 activation through phosphorylation [59]. Notably, the expression of CDK14 was also upregulated in clinical EOC samples and its expression was found to enhance the accumulation of nuclear β-catenin [60]. Therefore, the upregulation and association of cyclin Y and CDK14 in EOC may promote canonical Wnt signalling.…”
Section: Introductionmentioning
confidence: 99%
“…In glioma, the level of miR-128-3p expression was dramatically attenuated in glioma clinical tissues, and miR-128-3p regulated the progression of glioma via targeting NPTX1 and activating the IRS-1/PI3K/ AKT signaling pathway [12]. Cyclin-dependent kinase 14 (CDK14) is a member of cyclin-dependent kinases, and a previous study demonstrated that CDK14 was augmented in the tissues and cells of OC [13].…”
Section: Introductionmentioning
confidence: 99%